An Analysis of the Defense Acquisition System of the Israeli Defence Forces (IDF) - 이상승; 이창인; 정민섭; 박상혁 (International Journal of Advanced Culture Technology(IJACT), 2023)
The Israeli military's track record boasts victories in four Middle East wars and numerous counter-terrorism battles. This can be attributed to the implementation of a flexible defense acquisition system, allowing for the rapid acquisition of cutting-edge weaponry in response to ever-changing enemy vulnerabilities. If Korea were to adopt the defense acquisition system employed by the Israeli Defense Forces (IDF) it has the potential to transform into a small but strong country, mirroring the accomplishments of the IDF.